A new strategy for improving cytotoxicity of a copper complex toward metastatic melanoma cells unveiled by EPR spectroscopy. Issue 14 (24th March 2023) - Vieira, Eduardo Guimarães; Fazzi, Rodrigo Boni; Martins, Daniel O. T. A.; Sheveleva, Alena M.; Tuna, Floriana; da Costa Ferreira, Ana Maria
Abstract : An oxindolimine-copper(ii ) complex with antitumor properties was immobilized in a silica matrix, and verified to be more active and selective due the formation of a dinuclear species, unveiled by continuous wave and pulsed EPR spectroscopy. Abstract : A novel strategy of improving cytotoxicity against metastatic melanoma cells using an oxindolimine copper(ii ) complex immobilized and dimerized on a modified Polyhedral Oligomeric Silsesquioxane (POSS) matrix was developed, as revealed by electron paramagnetic resonance (EPR) spectroscopy. An assured correlation between continuous-wave (CW) and pulsed EPR spectroscopies provided a complete characterization of the actual active species, its coordination environment, as well as the efficiency/selectivity of the bioconjugate materials.